THE INTERCONNECTION OF RELIGION WITH COMMUNISM - Jannah, Miftahul; Aufa Rusydah, Layyin Aro; Tridara, Silvia Anugrah; Mubaraq, Zulfi (UNIVERSITAS PGRI TULUNGAGUNG, 2024)
The study of the Interconnection of Religion and Communism is very important to study in more depth. This is because these studies never stop being debated. The aim of this article is to understand 3 things: First, the paradigm of the Interconnection of Religion with Communism. Second, the internal and external factors that influence the Interconnection of Religion with Communism. Third, the positive and negative implications of the Interconnection of Religion with Communism on people's lives. The method used is qualitative with a literature approach based on theory, while data collection is by observing, identifying and reviewing data originating from journal literature and books and analyzed using data collection techniques and exploring data sourced from primary and secondary data sources. 3 things were found: First, the paradigm of Interconnection of Religion with Communism has 3 forms: (1) separate interconnection (2) connected interconnection and (3) inclusive interconnection. Second, internally there are 3 factors that influence: (1) freedom (2) religious leaders (3) theology. Externally, there are 3 factors that influence: (1) Differences in Principles (2) Political Economy and (3) History of Conflict. Third, positive and negative implications for social life. There are 3 positive implications: (1) the creation of a society that does not differentiate between castes (2) the principles of economic justice and (3) advancing religious freedom. Meanwhile, there are 3 negative implications: (1) chaos, (2) hostility and (3) hatred. The conclusion of this article shows that apart from having a bad impact, communism also has several benefits in social life if it is carried out with good intentions.